FORMING THE STUDENT'S ECOLOGICAL THINKING IN THE LESSON DURING THE TEACHING OF "NATURAL SCIENCE" IN THE 4TH GRADE - Sunnatullo Do'stov (Journal Park Publishing, 2023)
This article describes in forming the student's ecological thinking in the lesson during the teaching of "Natural Science" in the 4th grade, the reforms being carried out in our country in the formation of environmental culture through the teaching of geography in secondary schools, and the fact that environmental problems are gaining global importance.
Keywords: natural science, ecological culture, global importance, ecological thinking, ecology.